(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2017)
The most outstanding buildings of the Chinese People’s Republic for the last decade are observed. The contemporary projecting and construction techniques with the use of steel structures are analyzed for large-scale projects. Keywords:Chinese building megaprojects, construction, large-span steel structures